Lembaga Filantropi dan Fiskal Sebagai Instrumen Pembangunan Ekonomi Negara - Puput Triani; Santika Dewi; Parij Niamullah; Mohammad Ridwan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Economic development is the main goal that every country wants to achieve to improve people's welfare, reduce poverty, and encourage sustainable economic growth. This study examines the important role of philanthropic institutions and fiscal policy in encouraging economic development, both in general and from an Islamic economic perspective. Philanthropy, through voluntary contributions such as zakat, infaq, alms, and waqf, helps fill gaps that cannot be fully addressed by the public sector, improves people's welfare, and reduces socio-economic disparities. Fiscal policy, as the main tool of government, plays an important role in managing state revenues and expenditures, influencing economic growth, income distribution, and macroeconomic stability. Through in-depth literature analysis, this research finds synergies between the philanthropic sector and fiscal policy that can strengthen sustainable economic development. This study also provides insight into the development of Islamic economics in the last three decades, showing significant progress in academic research and operational practice. It is hoped that the results of this research can provide significant policy recommendations to maximize the potential of these two tools in achieving fair and sustainable economic development.